Republic of Poland : Technical Note on Impaired Loans. (IMF Staff Country Reports; Country Report ;, 2013)
This Technical Note analyzes impaired loans in Poland. Asset quality has moved up the Polish supervisor's agenda to address persistent impaired loans and cyclical deterioration in credit quality. Although the deterioration has been mainly observed in the quality of consumer loan portfolio, the foreign exchange mortgage loan portfolio also presents vulnerabilities that lie in exposure to foreign exchange risk. Tax disincentives, interest income accrual practices, underdeveloped securitization markets, and impediments in out-of-court restructurings impede rapid progress in cleaning up bank balance sheets. A recent loosening of underwriting standards for retail loans could contribute to rising inflows into impaired loans.